Fluorescence Quenching of the Fluorophore Diphenylamine for Determination of Neodymium (III) - Tahir, Tara F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Advanced analytical techniques such as Inductively Coupled Plasma Mass Spectrometry (ICP-MS) are powerful tools for chemical analysis; however, they present several practical challenges, including high operating costs, the need for skilled personnel, and time-consuming procedures for analysis and data interpretation. Their performance can also be affected by sample matrix interference, limited throughput, strict calibration requirements, and environmental concerns related to hazardous solvent disposal. Therefore, the development of a simple, sensitive, and cost-effective method such as fluorometry is highly desirable. In this study, fluorometry was applied for the determination of neodymium (III) based on the quenching mechanism of the fluorescent agent diphenylamine (DPA) in an ethanol medium. Neodymium, a lanthanide element, is important due to its environmental, industrial, and technological impacts. The fluorescence signal of DPA, excited at 310 nm, is quenched by Nd(III) in the presence of 2.2 mL of Britton–Robinson buffer at pH 3.0, forming a stable ion-associated complex. The method showed linearity over the concentration range of 0.5–24.0 μg/mL, with a limit of detection of 0.046 μg/mL and a limit of quantification of 0.140 μg/mL, and a strong correlation coefficient (R² = 0.9956). The tolerance of common coexisting substances was evaluated, and the results were consistent with those obtained using ICP-MS, confirming the method’s accuracy and precision, indicating that it is a reliable, simple, and effective tool for environmental monitoring and analysis.